2022
DOI: 10.1016/j.artd.2022.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Institution and COVID-19 on Access to Adult Arthroplasty Surgery

Abstract: Background Although insurance status is important to patients’ ability to access care, it varies significantly by race, age, and socioeconomic status. COVID-19 negatively impacted access to care, while simultaneously widening pre-existing health care disparities. The purpose of the current study was to document this phenomena within orthopedics. Methods Patients undergoing hip or knee arthroplasty at two medical centers in San Francisco, California were evaluated. One c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…According to the literature review on orthopaedic services alone in the first phase of the pandemic, the number of elective operations, trauma procedures and outpatient visits decreased by 80%, 47% and 63%, respectively 33 . US study showed that COVID-19 decreased access to hip and knee arthroplasties and also worsened pre-existing disparities: most affected were non-English speakers and people without a private insurance were most affected 22 . Similar findings are presented in a study on the use of oncology and cardiology services in Italy in March 2020 34 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature review on orthopaedic services alone in the first phase of the pandemic, the number of elective operations, trauma procedures and outpatient visits decreased by 80%, 47% and 63%, respectively 33 . US study showed that COVID-19 decreased access to hip and knee arthroplasties and also worsened pre-existing disparities: most affected were non-English speakers and people without a private insurance were most affected 22 . Similar findings are presented in a study on the use of oncology and cardiology services in Italy in March 2020 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Com a diminuição do pico da infecção da pandemia o número de pacientes à espera de artroplastia aumentou, com deterioração das condições clínicas e piora da qualidade de vida destes pacientes (Hanilton et al, 2022, Soriano & Toogood, 2022. Apesar dos desafios encontrados, hospitais públicos de Hong Kong continuaram fornecendo artroplastia àqueles pacientes de alta prioridade, com medidas de controle da contaminação (Lee et al, 2021).…”
Section: Introductionunclassified
“…While the pandemic is hopefully waning, this issue has 2 informative articles about the impact of COVID-19 on access to surgery and the effect of vaccination status on postoperative symptomatic COVID-19 after elective arthroplasty [ 2 , 3 ]. Other highlights include a study looking at the effectiveness of resorbable beads in treatment of infection with debridement and implant retention [ 4 ] and another article investigating patients’ perception of their scar after different surgical approaches for hip arthroplasty [ 5 ].…”
mentioning
confidence: 99%